(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A study on the effect of oligo-alginate produced by electron-beam on the growth and yield of wheat was carried out. A 700kGy dose of irradiation was used to degrade the dry powder of alginate and 100, 200 & 300 ppm concentration of aqueous solution was prepared